UNDERSTANDING WELFARE CRISES: THE ROLE OF IDEAS. (14th November 2013) - KUISMA, MIKKO
<x xml:space="preserve">Abstract</x> This symposium explores the role of ideas in welfare crises and transformations. Some of the key concerns are introduced in this article. First, it is argued that, rather than developing intentionalist accounts that explore ways in which elites use ideas as strategic tools, we should also pay attention to how ideas are expressed in public philosophies, collective memories, and logics of appropriateness. Second, it argues that crisis narratives are too often discussed in terms of 'times of crises'. In other words, crises are seen as events frozen in time and that a more temporally nuanced approach to crises is required in order to achieve a deeper understanding of their role in welfare reform. Finally, as the role of individual responsibility increases and the role of the state decreases, ideational accounts of welfare crises need to take seriously the impact of reform on everyday lived experiences of the citizenry.